2015
DOI: 10.1007/s12011-015-0476-3
|View full text |Cite
|
Sign up to set email alerts
|

Counteraction of Apoptotic and Inflammatory Effects of Adriamycin in the Liver Cell Culture by Clinopitolite

Abstract: Growing evidence has been reported on adriamycin (ADR) hepatotoxicity in literature. Hepatotoxicity caused by the use of drugs has a serious undesirable effect in the cure of cancer patients that needs to be eliminated. The exact mechanism of ADR on non-cancerous tissue still remains to be a mystery. The zeolite (clinoptilolite) minerals form a complex group of aluminosilicates that often occur as accessory minerals in intermediate and basic rocks. In light of this information, we investigated the possible ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The number of macrophages and fibroblasts, which play an essential role in wound healing, were higher in the control group when compared to the study group, although not statistically significant. These cells gradually increase in number in the early phase of the healing process, reach their peak levels, and gradually reduce in number as the healing process progresses (23).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The number of macrophages and fibroblasts, which play an essential role in wound healing, were higher in the control group when compared to the study group, although not statistically significant. These cells gradually increase in number in the early phase of the healing process, reach their peak levels, and gradually reduce in number as the healing process progresses (23).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…DOX tends to accumulate in mitochondria, causing changes in their structure and function. However, the main cause of DOX side effects observed in human is an extremely high level of oxidative stress within the cell, eventually causing apoptotic cell death [ 15 , 16 ]. A generation of free radicals caused by DOX can be described in two ways.…”
Section: Introductionmentioning
confidence: 99%
“…Acute drug-exposure is suggested to cause ROS generation from complex I at ETC in mitochondria [13], as well as the initiation of apoptosis [50]. With this knowledge, our previous studies have shown that antioxidant supplementation might be an excellent candidate to moderate DOX's toxicity [51][52][53][54][55][56].…”
Section: The Acute Toxic Effect Of Doxorubicinmentioning
confidence: 99%